Social stigmatisation in late identified patients with disorders of sex development in Indonesia. Issue 1 (30th October 2017) - Ediati, Annastasia; Juniarto, A Zulfa; Birnie, Erwin; Okkerse, Jolanda; Wisniewski, Amy; Drop, Stenvert; Faradz, Sultana M H; Dessens, Arianne
Abstract : Objectives: To assess social stigmatisation related to atypical appearance of the body, including, but not limited to the external genitalia, among Indonesian patients with a disorder of sex development (DSD). Until recently, diagnostic evaluation, information about the underlying causes of DSD and treatment options were sparsely available for these patients. Methods: Eighty-one parents of children and adolescents with DSD (aged 6–17 years) and 34 adult patients with DSD (aged 18–41 years) completed the Social Stigmatisation Scale towards DSD, an instrument developed to assesses the frequency of stigmatisation and the level of stress associated with these experiences. Open-ended questions investigated detailed information on stigmatisation as well as parents' and patients' emotional and behavioural reactions to these experiences. Differences in stigmatisation were explored across sex of rearing, gender change history, treatment status and DSD characteristics that could be easily identified by others (e.g., masculinisation of the body in women). Results: Social stigmatisation was reported by patients with atypical appearance of their genitalia, atypical appearance of their body aside from their genitals, among those who displayed cross-gender behaviour and those who changed gender. Among participants reared as women and among children and adolescents who changed gender, social stigmatisation was associated with ostracism, depressive symptoms and social isolation. Conclusions: Patients unable to conceal their condition (those with visible physical atypicality and those who changed gender) experienced social stigmatisation. Stigmatisation was stressful and related to isolation and withdrawal from social interaction. Education about DSD, self-empowerment and medical interventions to prevent atypical physical development may remove barriers to acceptance by others for affected individuals.